Robot‐assisted beating‐heart surgery for atrial septal defect repair in a case of situs inversus totalis with dextrocardia. Issue 5 (5th July 2021) - Li, Xin; Liu, Zhuang; Kong, Ruirui; Zhang, Chengxin; Ge, Shenglin
Abstract: Background: This paper describes a case of a patient with situs inversus totalis (SIT) and dextrocardia in which robotic atrial septal defect (ASD) repair was successfully performed in a beating heart. Methods and Results: A 45‐year‐old female patient who had SIT and dextrocardia was diagnosed with secundum ASD 5 years ago. Because of progressive dyspnoea, fatigue, and obvious cough, she came to our hospital for surgical treatment. Transthoracic echocardiography showed the defect located in the middle and lower segments of the atrial septum with a maximum diameter of 27 mm, with a left‐to‐right shunt. Transcatheter ASD closure could not be performed because there was not enough tissue surrounding the defect. After communicating with the patient, we performed robotic ASD repair in a beating heart using the da Vinci surgical system. The operation was successful, and the patient recovered quickly. Conclusion: As a minimally invasive approach, robotic cardiac surgery has many advantages and is feasible and safe in suitable patients.